A simple, sensitive, and low‐cost FACS assay for detecting antibodies against the native SARS‐CoV‐2 spike protein. Issue 3 (12th May 2021) - Hambach, Julia; Stähler, Tobias; Eden, Thomas; Wendt, Dorte; Tode, Natalie; Haag, Friedrich; Tolosa, Eva; Altfeld, Marcus; Fathi, Anahita; Dahlke, Christine; Addo, Marylyn M.; Menzel, Stephan; et al.
Abstract: Background: Hamburg is a city state of approximately 1.9 Mio inhabitants in Northern Germany. Currently, the COVID‐19 epidemic that had largely subsided during last summer is resurging in Hamburg and in other parts of the world, underlining the need for additional tools to monitor SARS‐CoV‐2 antibody responses. Aim: We aimed to develop and validate a simple, low‐cost assay for detecting antibodies against the native coronavirus 2 spike protein (CoV‐2 S) that does not require recombinant protein or virus. Method: We transiently co‐transfected HEK cells or CHO cells with expression vectors encoding CoV‐2 S and nuclear GFP. Spike protein‐specific antibodies in human serum samples bound to transfected cells were detected with fluorochrome conjugated secondary antibodies by flow cytometry orimmunofluorescence microscopy. We applied this assay to monitor antibody development in COVID‐19 patients, household contacts, and hospital personnel during the ongoing epidemic in the city state of Hamburg. Results: All recovered COVID‐19 patients showed high levels of CoV‐2 S‐specific antibodies. With one exception, all household members that did not develop symptoms also did not develop detectable antibodies. Similarly, lab personnel that worked during the epidemic and followed social distancing guidelines remained antibody‐negative. Conclusion: We conclude that high‐titer CoV‐2 S‐specific antibodies are found in most recovered COVID‐19 patients and in symptomatic contacts, but only rarely in asymptomatic contacts. The assay may help health care providers to monitor disease progression and antibody responses in vaccination trials, to identify health care personnel that likely are resistant to re‐infection, and recovered individuals with high antibody titers that may be suitable asplasma and/or antibody donors. Abstract : We report a low‐cost FACS assay for antibodies against the native severe acute respiratory syndrome coronavirus 2 spike protein that does not require recombinant proteins or infectious virus. We demonstrate the utility of the assay by assessing antibody responses of hospitalized patients, health care personnel, and house‐holds of coronavirus diasease 2019 + individuals and their co‐quarantined room mates in the city state of Hamburg